2013
DOI: 10.4238/2013.july.24.5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differential gene expression during floral bud abortion in radish (Raphanus sativus L.)

Abstract: ABSTRACT. Radish floral bud abortion (FBA) is an adverse biological phenomenon that occurs during reproduction. Although FBA occurs frequently, its mechanism remains unknown. To elucidate the molecular mechanism underlying FBA, we detected gene expression differences between aborted and normal buds of radish using cDNA-amplified fragment length polymorphism (AFLP) and real-time polymerase chain reaction (real-time PCR). A total of 221 differentially expressed transcript-derived fragments (TDFs) were detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Bud abortion is a very common biological phenomenon in Brassica species. During bud abortion, the buds stop growing, convert from green into yellow progressively from the base to the top of the bud, and eventually wither off before flowering [ 1 , 2 ], which is detrimental for hybrid seeds yield during cross breeding. In recent years, bud abortion has attracted considerable attention in Brassica species cross breeding [ 3 , 4 , 5 ], as it reduces the hybrid seed yield production of many Brassica crops and also affects the efficiency of Brassica crops cross breeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bud abortion is a very common biological phenomenon in Brassica species. During bud abortion, the buds stop growing, convert from green into yellow progressively from the base to the top of the bud, and eventually wither off before flowering [ 1 , 2 ], which is detrimental for hybrid seeds yield during cross breeding. In recent years, bud abortion has attracted considerable attention in Brassica species cross breeding [ 3 , 4 , 5 ], as it reduces the hybrid seed yield production of many Brassica crops and also affects the efficiency of Brassica crops cross breeding.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bud abortion has attracted considerable attention in Brassica species cross breeding [ 3 , 4 , 5 ], as it reduces the hybrid seed yield production of many Brassica crops and also affects the efficiency of Brassica crops cross breeding. In the past decade, to solve the bud abortion problem, many studies have investigated the factors that cause bud abortion [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. However, most of the studies focused on morphology and anatomy, and few studies have reported the factors contributing to Brassica bud abortion at the molecular level.…”
Section: Introductionmentioning
confidence: 99%